ANTI-DIABETIC ACTIVITY OF EPIPREMNUM AUREUM.L IN NORMAL AND ALLOXAN-INDUCED DIABETIC RATS - G, Abhinayani; Kishore R, Naga; Benazir, Fathima; Agarwal, Pooja (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The study was carried out with the objective of phytochemical screening and to evaluate the anti-diabetic activity of aqueous and alcoholic extract of E. aureum. Methods: The anti-diabetic activity was determined alloxan-induced diabetic rats. A total of 24 albino Wistar rats of either sex weighing 200-250 g were divided into 4 groups consisting of 4 rats in each group. Group-1 served as control, Group-2 received standard drug, Group-3 received test drug aqueous extract of E. aureum, and Group-4 received test drug alcoholic extract of E. aureum. Results: Phytochemical investigation of aqueous and alcoholic extracts of E. aureum revealed the presence of alkaloids, tannins, saponins, terpenoids, and flavonoids as secondary metabolites. The both aqueous and alcoholic extracts of E. aureum showed a significant reduction in blood glucose levels due to the presence of phytochemicals such as flavonoids, terpenoids, and alkaloids in both extracts of E. aureum. The administration of drug (IP) was continued upto 15 days. Conclusion: Extracts of E. aureum have shown the great potential of anti-diabetic activity in normal and alloxan-induced rats. Flavonoids might be producing hypoglycemic effect by a mechanism independent from insulin secretion, e.g. by the inhibition of endogenous glucose production or by the inhibition of intestinal glucose absorption. This study E. aureum of both aqueous and alcoholic extracts was showed significant effect on alloxaninduced rats. Keywords: Epipremnum aureum, Anti-diabetic activity, Alloxan-induced diabetic rats, Glucometer.